Molecular mechanisms governing the differentiation and expansion of myeloid-derived suppressor cells - Wang, Ke; Wang, Xiao; Sun, Nan (Frontiers in Cell and Developmental Biology, 2025)
Myeloid-derived suppressor cells (MDSCs) play critical roles in tumor immune evasion. These heterogeneous cells are broadly classified into granulocytic (G-MDSC), monocytic (M-MDSC), and their immature precursors, early-stage MDSCs (e-MDSCs). Elucidating their differentiation and expansion mechanisms is crucial for advancing cancer immunotherapy. This review examines the key signaling pathways (e.g., JAK/STAT, NF-κB, Notch), regulatory cytokines, metabolic factors, and epigenetic modifications central to MDSC biology. A comprehensive understanding of these intricate networks provides valuable insights into tumor immune evasion and facilitates the identification of novel therapeutic targets designed to overcome MDSC-mediated immunosuppression.